LOAN BROKERS - Adela IONESCU (Challenges of the Knowledge Society)
A loan is probably the most important financial decision we make in life. In a time when lack of time affects us in every way, including financially, we can only appeal to specialists if we want fast, reliable and quality long-term services. „The notion of “creditor” includes all legal entities, branches of credit institution and nonbankingfinancial institutions that operate in Romania and grant or undertake to grant loans in itscommercial of professional activity”. In the case of loans, the "specialist" has been called loan broker. Loan broker is a person trained in intermediating bank loans who offers advice on choosing the best financial solutions for each client. Through partnerships with banks in Romania, the broker has access to their credit products and assist customers in choosing the loan that best suits their financial needs and possibilities. Moreover, the broker will help in preparing loan application to be submitted to the bank and pursue it to its completion. Loan broker can be defined as the person authorized by the bank or non-bank financial institutions to promote their products through direct contact with natural or legal persons wishing to contract a loan, without any of the parties to have exclusivity. There can be defined as an independent bank or non-bank financial institution, as an intermediary between customers and banks. Through its financial advisors , the company helps customers overcome the difficulty of understanding the credit products, difficulties arising from the multitude of factors that compose such a product, especially in the case of a housing loan or mortgage. Each financial institution is doing everything possible through such partnerships to attract the largest possible portfolio of clients, therefore is developing a real network of brokers to be partners for local or national level (depending on the sites coverage of the branches of each institution) on one or more types of credit products. The loan broker advises individuals and businesses in choosing and contracting the most appropriate credit and handles the relationship with the bank (collection and submission of documents, monitoring of file analysis, informing the customer). He is not allowed to approve or reject a case, this decision lies with the bank that takes the file for analysis.